'Nowhere to be found’: disabled refugees and asylum seekers within the Australian resettlement landscape - Buckley, Amma; Soldatic, K.; Somers, K.; Fleay, Caroline (The Critical Institute, 2015)
Australia has long placed restrictions on the immigration of people with disabilities. While recent civil society mobilisation has forced some shift in policy, it is far from clear whether this will result in people with disabilities being accepted as immigrants. The issue is complicated further for people defined as ‘refugees’ and ‘asylum seekers’ who have encountered the migration restrictions on disability. As a result of this policy landscape, there is limited rigorous research that seeks to understand the social inclusion and participation of disabled refugees and asylum seekers within the resettlement process. An extensive review reveals that refugees and asylum seekers with disabilities remain largely absent from both resettlement literature and disability research. This paper summarises the limited available research in the area around the following themes: processes of offshore migration and the way that disability is assessed under Australia’s refugee legislation; the uncertainty of the prevalence of disability within refugee and asylum seeker communities; the provision of resettlement services, both mainstream and disability-specific, through the transitional period and beyond; and the invisibility of asylum seekers with disabilities in Australia’s immigration detention centres, community-based arrangements and offshore processing centres. To conclude, the paper outlines implications for further research, policy and practice in the Australian context.